Immunohistochemical basis for FAP as a candidate theranostic target across a broad range of cholangiocarcinoma subtypes - Laura C. Jorgenson; Michael S. Torbenson; Thorvardur R. Halfdanarson; Lionel A. Kankeu Fonkoua; Nguyen H. Tran; Lewis R. Roberts; Rory L. Smoot; Ajit H. Goenka; Scott M. Thompson (Frontiers in Nuclear Medicine, 2024)
PurposeThe aims of this study were to evaluate and compare fibroblast activation protein (FAP) expression and localization in surgically resected cholangiocarcinoma (CCA), primary and metastatic hepatocellular carcinoma (HCC), hepatocellular adenoma (HCA), and focal nodular hyperplasia (FNH), and to identify any association between CCA clinical or pathologic features and FAP expression.Materials and methodsFAP immunostaining from surgically resected CCA (N = 58), primary intrahepatic and extrahepatic metastatic HCC (N = 148), HCA (N26), and FNH (N = 19) was scored (negative, weak positive, moderate positive or strong positive) from tissue microarrays. FAP expression was compared between groups. CCA FAP expression was compared to clinical and tumor pathology features.ResultsModerate-strong FAP expression in the tumor stroma was present in 93.1% of CCA, 60.7% of extrahepatic metastatic HCC, 29.6% of primary HCC, 21.1% of FNH, and 11.6% of HCA. Moderate-strong FAP expression in tumor stroma was significantly more prevalent in CCA than HCC (p < 0.001), metastatic HCC (p = 0.005), HCA (p < 0.001) and FNH (p < 0.001). FAP was expressed in the stroma of all but one CCA (1.7%), and FAP expression in CCA tumor stroma was not associated with any clinical or tumor pathology features (p > 0.05, all).ConclusionFAP is expressed in the stroma of a high proportion (93%) of primary CCA independent of patient clinical or tumor pathology features. As such, these data provide the tissue basis for systematically evaluating FAP as a theranostic target across a broad range of CCA subtypes.